Fanconi Syndrome: Genetic and Acquired Determinants - Rejmak, Rafał; Karamus, Kornelia; Biłogras, Jan; Urban, Wojciech; Borowska-Łygan, Martyna; Strużek, Konrad; Tomaszewski, Jakub (Journal of Education, Health and Sport, 2025)
Fanconi syndrome is a condition characterized by proximal tubular dysfunction of the nephron, leading to urinary loss of glucose, amino acids, and electrolytes such as phosphate, sodium, potassium, calcium, and magnesium. It often co-occurs with tubular acidosis and a decreased level of the active form of vitamin D in the blood. Fanconi syndrome is associated with various conditions, both inherited and acquired, and may also occur as a side effect of certain medications. Inherited causes of Fanconi syndrome include conditions such as cystinosis, Wilson's disease, Dent disease type I, Lowe syndrome, tyrosinemia type I, galactosemia, and Fanconi-Bickel syndrome. Acquired forms are linked to drug toxicity, including anticancer agents, antibiotics, chelating agents, and antiviral drugs. The syndrome may also develop in the context of monoclonal gammopathies, heavy metal intoxication, or exposure to aristolochic acids present in certain herbal remedies. The treatment of Fanconi syndrome primarily focuses on addressing the underlying cause and may involve both symptomatic management and targeted therapy. Early diagnosis in children is crucial to prevent bone damage and growth disturbances. This article provides a comprehensive review of the pathophysiology, clinical presentation, underlying causes, and management of Fanconi syndrome, with an emphasis on both inherited